Classifying Linux Memory Consumption Patterns Based on Self-Organizing Maps - Lin, Mauricio T. N. G.; Mota, Edjard de S.; Biris, Ilias (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2007)
The problem of memory exhaustion with restricted memory still sparks long discussions inside the Linux kernel developers community. The current implementation to treat the memory exhaustion in Linux is named as Out of Memory Killer and its algorithm to select processes for termination requires more investigation in terms of memory consumption behaviour. This paper describes a methodology to classify memory consumption patterns of Linux applications based on a neural network model known as Self-Organizing Maps. A tool was developed to provide the practical opportunity to apply this mechanism for the classification of memory consumption patterns related to real Linux applications use cases.